MECHANISM OF HEXANE DEHYDROCYCLIZATION TO BENZENE USING BI-FUNCTIONAL REFORMING CATALYST - Abdul Salim Nasution (Scientific Contributions Oil and Gas, 1991)
The Mechanism of n. hexane dehydrocyclization reaction to benzene has beenstudied with pure hydrocarbons and synthetic naphtha feedstock at the operating conditions: T = 400° - 520°C PT = 10 – 30 kg/cm2 and H2/HC = 4-10 mole/mole using a Catatest Unit operated in a continuous system. The results show that n, hexadiene has been formed as a mayor source of the intermediate molecule of the methylcycloamil ion, an optimum metal site activity was observed for a given acid-site of bi-functional reforming catalyst and – 1 (minus one) of the total reaction order of n. hexane dehydrocyclization to benzene.